Aberrant Methylation of Aging-Related Genes in Asthma - Yang, Yu; Yuan, Lin; Yang, Ming; Du, Xizi; Qin, Ling; Wang, Leyuan; Zhou, Kai; Wu, Mengping; He, Ruoxi; Feng, Juntao; Xiang, Yang; Qu, Xiangping; et al. (Frontiers in Molecular Biosciences, 2021)
Background: Asthma is a complex pulmonary inflammatory disease which is common among older adults. Aging-related alterations have also been found in structural cells and immune cells of asthma patients. Nonetheless, the underlying mechanism by which differenced aging-related gene contributes to asthma pathology remains unclear. Of note, DNA methylation (DNAm) have been proven to be play a critical mechanism for age-related gene expression changes However, the methylation changes of aging-related genes in asthma patients is still obscure. Methods: First, changes in DNAm and gene expression were detected with multiple targeted bisulfite enrichment sequencing (MethTarget) and qPCR in peripheral blood of 51 healthy controls (HCs) and 55 asthmatic patients. Secondly, the correlation between the DNAm levels of specific altered CpG sites and the pulmonary function indicators of asthma patients was evaluated. Lastly, the Receiver Operator Characteristic (ROC) curve and Principal Component Analysis (PCA) were used to identify the feasibility of the candidate CpG sites as biomarkers for asthma. Results: Compared with HCs, there was a differential mRNA expression for 9 aging-related gene in peripheral blood of asthma patients. Besides, the methylation level of the 9 aging-related genes were also altered in asthma patients, and a total of 68 CpG sites were associated with the severity of asthma. Notably, 10 of the 68 CpG sites were significantly associated with pulmonary function parameters. Moreover, ROC curve and PCA analysis showed that the candidate differential methylation sites (DMSs) can be used as potential biomarkers for asthma. Conclusions: In summary, this study confirmed the differentially expressed mRNA and aberrant DNAm level of aging-related genes in asthma patients. The differential DMSs are associated with the clinical evaluation indicators of asthma, which indicate the involvement of aging-related genes in the pathogenesis of asthma and provide some new possible biomarker for asthma.